Changing densities of generalist species underlie apparent homogenization of UK bird communities. (13th May 2016) - Sullivan, Martin J. P.; Newson, Stuart E.; Pearce‐Higgins, James W.
Abstract : Generalist species are becoming increasingly dominant in European bird communities. This has been taken as evidence of biotic homogenization, whereby generalist 'winners' systematically replace specialist 'losers'. We test this pattern by relating changes in the average specialization of UK bird communities to changes in the density of species with different degrees of habitat specialization. Although we find the expected decline in community specialization, this was driven by a combination of a strong increase in the density of the most generalist quartile of species and declines in the density of moderately generalist species. Contrary to expectation, specialist species increased slightly over the 18‐year study period but had little effect on the overall trend in community specialization. Our results indicate that the apparent homogenization of UK bird communities is not driven by the replacement of specialists by generalists, but instead by the changing fortunes of generalist species.